Assessing the impact of vaccines on COVID-19 efficacy in survival rates: a survival analysis approach for clinical decision support - González Rodríguez, Juan Luis; Oprescu, Andreea M.; Muñoz Lezcano, Sergio; Cordero Ramos, Jaime; Romero Cabrera, Juan Luis; Armengol de la Hoz, Miguel Ángel; Estella, Ángel (Frontiers in Public Health, 2024)
BackgroundThe global COVID-19 pandemic, caused by the SARS-CoV-2 virus, has presented significant challenges to healthcare systems worldwide.ObjectiveThis study, based on an analysis of a cohort from the Public Health System of Andalusia (Spain), aims to evaluate how vaccination affects case-fatality rate in patients hospitalized due to COVID-19 infection in Andalusia.MethodsThe cohort consists of 37,274 individuals after applying the inclusion criteria. We conducted survival analyses employing the Cox proportional hazards models and generated adjusted survival curves to examine the outcomes. The analyses were performed from three perspectives: vaccinated vs. unvaccinated patients, vaccinated and unvaccinated patients grouped by age, and stratified by vaccination status.ResultsResults indicate a substantial correlation between vaccination and a 20% reduction in the risk of case-fatality. Age-specific effects reveal varying degrees of protection across different age groups.ConclusionThese findings emphasize the pivotal role of vaccination status in COVID-19 risk assessment, supporting the development of a clinical decision support system for accurate predictions and optimizing healthcare management at admission.